NILAI-NILAI PENDIDIKAN ISLAM DALAM MODEL PEMBELAJARAN BUDAYA - Yunus Bayu (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2021)
This study aims to determine the value of Bugis culture in Islamic education at Tana Luwu higher education institutions in Palopo City, namely Andi Djemma University, IAIN Palopo. This study uses a qualitative method with an ethnopedagogical approach. Building religious harmony in the value of local wisdom education is still very relevant to be applied by all students. This is reflected in the attitude of students through discipline and responsibility. Discipline and responsibility of students to maintain self-esteem, dignity. A reflection of plurality which functions as a student's spirit in the process of values ​​education. The concept of cultural learning in Islamic religious education provides respect for values ​​such as Sipakatau (giving each other information), Sipakalebbi (Mutual respect), Sipakingge (Reminding each other), Sipakatou (Sharing each other). Appreciate peace, happy to help others, especially if they are fellow human beings. So that Bugis cultural education is in line with the plurality values ​​that grow and develop in Indonesia